MENUJU PENDIDIKAN NONFORMAL BERKUALITAS DENGAN MOTIVASI, KOMPETENSI, DAN KUALIFIKASI PTK PNF - Widayati, Tri (JIV-Jurnal Ilmiah Visi, 2007)
The quality of non-formal education depends on the quality and the role of educators and education staff (PTK-PNF). Institutionally, The Government has implemented strategic plans to develop the qualification and competency of educators and education staff of non-formal education through a set of trainings and degree programs. These programs will be fruitful in improving the competency if PTK-PNF is not motivated to improve their performance. This article suggests building â€œVirus NAchâ€ in PTK-PNF. There are three strategies to create achievement motivation: (1) rational-empiric, (2) normative-educative, and (3) force-power. The emergence of N-Ach PTK-PNF must be balanced by the growth of â€œsocial virusâ€ in PNF institution, so structural obstructions will not impede creativity achievement to provide PNF services with a high quality.